THE ASSESSMENT OF SOIL PHOSPHATE AVAILABILITY USING SORPTION CURVE ON NEWLY OPEN LOWLAND AREAS - KASNO, ANTONIUS; SULAEMAN, .; DWINININGSIH, SUTISNI (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2000)
Rice growth in the newly open lowland areas is restricted, especially nutrients availability. The purposes of the research as to study the sorption of soil P and soil P availability rice growth of the newly lowland. The field experimental is located at Dwijaya, Tugumulyo, Musi Rawas, South Sumatra province. Soil P-sorption was analysed in the laboratory for wet and dry soil samples, with two CaCI2 concentration (i.e.: 0.01 and 0.005 M). Soil fertility status of experimental site is very poor with N, P, K, Ca, Mg and organic matter as limiting factors for crop growth. Maximum rice yield in the site was achieved by P fertilizer application of 767 kg of SP-36, and correspond to available soil P (Bray 1) content of 5 ppm P. The phosphorus standard requirements in 0.01 and 0.005 M CaCI2 extracting solution are found to be 0.0051 and 0.0018 ppm P for wet soil sample and 0.009 and 0.003 ppm P for dry soil sample respectively.